Spatio-temporal distribution of soil microbial communities and nutrient availability around a municipal solid waste landfill - Mingye Zhan; Yanqiu Sun; Huanjie Lan; Tao Zhou; Youcai Zhao; Li Yang (Frontiers in Microbiology)
IntroductionThe landfills may have notable ecological impacts on the surrounding environment, yet little is known about the microbial community and nutrient conditions in surrounding soil.MethodsUsing high-throughput sequencing technology, we analyzed the spatio-temporal distribution of bacterial and fungal communities in soils surrounding a large-scale landfill. The component of landfill waste and twelve soil properties were detected, including four nutritional indices and eight heavy metal elements.Results and discussionOur results revealed landfill-specific enrichment of bacterial genera Pseudomonas (0.13–6.43%), Marmoricola (0.12–4.82%), Sphingomonas (0.64–5.24%), and Nocardioides (0.51–6.3%) and fungal genera Alternaria (0.23–12.85%), Pyrenochaetopsis (0.028–10.12%) and Fusarium (0.24–4.07%). Their relative abundances exhibited significant variations across landfill age gradients and soil depth profiles (p ≤ 0.05). Random forest and structural equal models (SEM) confirmed the direct correlation between soil TOC, heavy metals including Cu, Cd and Pb and microbial diversity. While soil heavy metals mainly exhibited negative effects on microbial diversity, dominant microbial taxa such as Lysobacter, Nocardioides, Pseudopithomyces, and Chaetomium showed potential tolerance to heavy metal stress in soil around the landfill. In soil around the landfill, higher concentrations of total nitrogen (TN), available phosphorus (AP) and available potassium (AK) were observed in the upper layers near the aged landfill areas, whereas higher concentration of total organic carbon (TOC) were detected around fresh landfill area. The distribution of microbial taxa and predicted functional profiles were strongly associated with the nutrients availability. The findings revealed that landfill activities influenced the structure and function of microbial community, contributing to the complex spatio-temporal distribution of nutrients in the surrounding soil.